From the Ashes of the Bronze Age: Thermally Altered Human Remains from Iron Age (Cypro-Geometric and Cypro-Archaic) Mortuary Contexts in Cyprus - Branca, Natalie M. (Journal of Mediterranean Archaeology, 2024)
This paper surveys the published evidence for thermally altered human remains on Cyprus from mortuary contexts dating to the Iron Age (Cypro-Geometric and Cypro-Archaic periods), while outlining new theoretical perspectives and scientific approaches resulting from the development of analytical methods that have expanded the potential for specialists to study such remains on the island through the lens of funerary taphonomy. Most of our current knowledge of ancient fire-related bodily transformations such as cremation comes from regions where thermally altered human remains are frequently found in archaeological contexts. For some geographical regions, however, the use of fire in mortuary contexts remains underexplored, and this is the case with Cyprus, where thermally altered human remains are rarely recovered. I survey previous research on the subject, although the true extent of fire-related mortuary practices on the island is currently unknown. I address current challenges and suggest potential directions for future research.